Development of a melanoma therapeutic vaccine candidate by the coencapsulation of melanoma antigen peptides and toll-like receptor ligands as adjuvants into polymeric nanoparticles - Silva, Joana Catarina Mendão Azeitão da, 1985- (2014)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014